ความต้องการใช้สื่อการเรียนรู้ออนไลน์ ด้านศิลปะและวัฒนธรรมภาคใต้และคาบสมุทรสยาม-มลายูของนักศึกษาในเครือข่าย MOU สามมหาวิทยาลัย - จรรยา หีดแก้ว (มหาวิทยาลัยสงขลานครินทร์, 2023)
This study was conducted using a mix-methods approach, with the objective of investigating and comparing the needs regarding the types, information and knowledge, and characteristics of online learning media related to arts and culture in the Southern Thailand and the Siamese-Malay Peninsula, among students in the MOU network of three universities. The research methodology was divided into two parts: 1) Quantitative Research: Data was collected from a sample group comprising the undergraduate students at Prince of Songkla University Hat Yai Campus, Thaksin University Songkhla Campus, and Rajamangala University of Technology Srivijaya Songkhla Campus, with a total of 395 students. The sample size was determined using the Yamane Formula (Yamane, 1970) and selected through the Proportionate Stratified Random Sampling to ensure representation according to the population size within each category. Subsequently, the Simple Random Sampling was applied, where the students were selected without replacement until the specified sample size was achieved.Data was collected using a questionnaire, with subsequent analysis employing frequency distribution, percentage, mean, and standard deviation.The study also compared the students’ needs for online learning media, across different categories including universities, genders, and year levels, by applying the F-values (F-Test) in a one-way analysis of variance (One-Way ANOVA). When statistically significant differences were detected at the .05 level, pairwise comparisons were conducted using the LSD (Least-Significant Different) method. 2) Qualitative Research: Data collection was performed with a sample group of 15 students from the MOU network of the aforementioned three universities. These participants were purposively selected from those with experience in using online learning media on the website NAAMCHOOP.COM, who consented to provide additional information via individual interviews within the questionnaire.The Simple Random Sampling method was employed using a non-replacement lottery approach for each university, until a group of five performants from each institution was achieved Semi-structured interviews were used as the data collection instrument, and the collected data was analyzed using content analysis techniques. The results of the study are summarized as follows. 1. The findings revealed a high level of needs among students for online learning media in the field of arts and culture within Southern Thailand and the Siamese-Malay Peninsula on the whole and across different aspects. The students’ higest needs were found to be related to the characteristics of the online learning media, followed by the media information and knowledge, with the media types being the least required. It was worth noting that students expressed a pronounced interest in online learning media that offer flexible accessibility to lessons at their convenience, as well as those which provide a wide array of language options. Moreover, when it came to media information and knowledge, students demonstrated a particular interest in traditions and rituals. Additionally, the preferred platform for accessing online learning content among students was found to be YouTube. 2. When comparing the level of needs for using online learning media on the whole and different aspects, it was apparent that students in different universities and with different genders exhibited varying degrees of needs for using online learning media at a significance level of .05. However, no statistically significant difference was observed among students with varying year levels. Furthermore, the study revealed that the students at Thaksin University Songkhla Campus with non-binary gender identities, and those in different years exhibited the highest overall needs for using online learning media. When it came to different aspects concerning universities, genders, and year levels; statistically significant differences were observed among the students' needs for online learning media regarding the type and information and knowledge of online learning media with a significance level of .05. Nevertheless, no statistically significant difference was found in terms of media characteristics. Regarding university-specific findings, the students at Thaksin University, Songkhla Campus displayed the highest needs for using online learning media in terms of the media types and media information and knowledge, whereas those at Prince of Songkla University, Hat Yai Campus expressed the highest needs concerning the characteristics of the media. In the context of gender-based analysis, the non-binary students exhibited the most substantial desire to use online learning media across all aspects. Analysis by year levels showed that the second-year students demonstrated the greatest enthusiasm for online learning media, particularly in their needs for the media types and media information and knowledge, whereas the third-year students displayed the highest needs regarding the media characteristics. 3. The students provided intriguing feedback regarding the Naamchoop.com website. They appreciated its visually appealing design, user-friendly interface, and engaging nature. However, they expressed concerns about the inadequacy of content and online learning media for studying and utilizing, especially media about arts and cultures of different countries in the Siam-Malay peninsula, which are much fewer than that in southern Thailand. Furthermore, the students voiced their desire to enhance the website's visibility and popularity, particularly among students within the MOU network of the three universities. Based on the findings, a set of guidelines can be formulated for the future development of online learning resources to be featured at the Naamchoop.com website of the Self-Access Learning Center, the Faculty of Liberal Arts at Prince of Songkla University.These guidelines should prioritize the development of online learning materials in the social media category, with a particular emphasis on the development of crucial information and knowledge pertaining to cultural traditions and rituals. Furthermore, the developed online learning resources must be designed for universal accessibility and offered a multitude of language options.